UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN KOOPERATIF TWO STAY TWO STRAY DI KELAS VIII4 SMP ISLAM AS-SHOFA - Fitrim Dilfa; Sehatta Saragih; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research based on the students’mathematics achievement at class VIII4 Junior High School Islam As-Shofa who haven’t reached passing grade on main topic about Phytagoras. One of the factors to improve students’mathematics achievement is improve learning process, so reacherch try to improve the process by applying Contextual Teaching and Learning on cooperative learning model of Two Stay Two Stray.The research is classroom action research. This aims research to increase learning process and students’ math achievement at class VIII4 Junior High School Islam As-Shofa through the implentation Contextual Teaching and Learning in cooperative learning Two Stay Two Stray (TSTS).The subject of the research are 24 students from class VIII4 Junior High School Islam As-Shofa with the heterogenous level. Instrument to collect the data are observation, attitude assessment sheet, skill assessment sheet and mathematics achivement test. The observation data analyzed by using descriptive and qualitative,and for students’test by using descriptiveand quantitative. The qualitative analysis showed an improvement of learning process prior to action to the first cycle and second cycle. The results of this research showed an increase in students achievement for attitude competence from the based-score with the percentage 41,67% to 58,30% on the first cycle and 87,50% on the second cycle. For knowledge competence showed an increase from the based-score with the percentage 29,17% to 37,50% on the first cycle and 70,83% on the second cycle. And for skills competence showed an increase from the based-score with the percentage 12,50% to 37,50% on the first cycle and 70,83% on the second cycle. Based on the finding can be concluded that the implentation of Contextual Teaching and Learning in cooperative learning Two Stay Two Stray could improve students’ mathematics achievement at class VIII4 Junior High School Islam As-Shofa in the second semester academic years2014/2015.Key Word : Students’ Mathematics Achievement, Contextual Teaching and Learning, Cooperative Learning Two Stay Two Stray, Classroom Action Research.